HIGH RESOLUTION DEM PRODUCTION USING MODIFIED INTERPOLATION METHODS (QUADRANT & OCTANT) - Tawfiq, Nabeel; Mahmood, Faleh; Muhsin, Israa (Iraqi Journal of Science, 2024)
A digital elevation model (DEM) is a digital file of terrain elevations for ground positions. It is a raster representation of the elevation of the ground and objects, such as buildings and trees, with pixel values in the images, as well as the wide range of uses and applications. In this research, the Easting, Northing, and Elevation, data set had been gathered, they collected by performing field survey using global Positioning system (GPS). Modified an interpolation method had been presented it depends on Quadrant and Octant methods to produce a DEM surface. Some classic techniques such as Nearest neighbor and universal Kriging, have been used for comparison purpose with the results of the new technique. A new technique has been used it depends on multilayer processing, mosaic model have been applied between the layers to perform the high resolution DEM. A 3-D image has been produced as one of the most important application of DEM.